Plantar center of pressure and postural balance according to head anteposition - León-Molina, Pamela; Pincheira-Barbé, Patricio; Gary-Bufadel, Alfredo; Contreras-Acevedo, Edwin; Frugone-Zambra, Raúl Ernesto (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: balance posture is noticeable in the variations occurring on the plantar center of pressure (COP) due to internal or external disorders. The objective of this study was to determine the limit of head anteposition in an antero-posterior direction to which a subject may be exposed to without significant modifications to plantar center of pressure and postural balance, conducting a pre-experimental study. Methods: a convenience sample of 30 healthy male subjects with aligned posture aged 20 to 25 years (22.6 ± 1.88) was selected. The following subjects were excluded: individuals taking drugs that affect posture and balance, who practiced intense physical activity 24 hours prior to the study or who suffered any disease of spine and lower extremities. The study complied with the Declaration of Helsinki and an informed consent was signed. To determine COP in orthostatic position, a force plate (Kistler model 9286BA) was used. Subjects were requested to take a bipedal position on the plate. A plumb line was placed over the tragus, in between subject and observer, recording oscillations for 30 seconds. The experiment was repeated by gradually inducing a head anteposition until reaching 5 centimeters. The Wilcoxon test was used to prove the null hypothesis. Results: the average displacement from the plantar center of pressure in orthostatic position per root mean square on the x-axis was 0,25170 and on the y-axis was 0,34987. With 1 cm of induced head antepopsition, the plantar center of pressure varied significantly to 0,23031 on the x-axis and 0,36576 on the y-axis. Conclusion: the minimum anterior displacement of skull significantly modifying the plantar center of pressure and postural balance is 1 cm.